Estudo da aplicação de mínima quantidade de fluido no fresamento de acabamento da liga Ti-6Al-4V - Garcia, Ubirajara [UNESP] (2015)
To reduce cutting fluids use in machining operations is one goal that has been searched in industrial companies, due to ecological and human health problems caused by the cutting fluid. However, the cutting fluids still provide a longer tool life for many machining operations. This is the case of Ti6Al4V titanium alloy end milling operation using coated carbide inserts. Therefore, this work objective is to study cutting conditions more suitable for minimum quantity of fluid technique use, i.e., conditions which make tool life in MQF technique, closer or over to that obtained with dry cutting and cutting with fluid fload, without damaging the workpiece roughness. To reach these goals several end milling experiments were carried out, varying up cutting speed and feed rate with MQF technique application with three different fluids compared with dry cutting and cutting with fluid fload. The main study conclusion was that applying the MQF technique in Ti-6Al-4V end milling process increases tool life, improving productivity and roughness, when kept up the same cutting conditions proposed originally